The nature of fee charged for provision of public services - M. Khoroshaylova (Правоприменение, 2018)
The subject. This paper is devoted to the study of the legal nature of fees charged by the public authorities for the provision of public services.The main aim of the paper is to substantiate the answer on the question is this fee a price or a fiscal charge?The methodology of the study includes general scientific methods (analysis, synthesis, description) as well as particular academic methods (formal-legal method, interpretation of legal acts). The decisions of Russian Constitutional Court are also analyzed.The main results and scope of their application. The article focuses on analysis of the features and functions of the government, ratio of functions of the government and functions of the public authorities, their powers. State power is exercised by bodies of state power or specially authorized entities on behalf of the state and in the public interest. It excludes the exchange nature of the relations when these bodies and entities implement state power. The nature of the establishment and collection of the fee excludes the equivalence between the size of fee and the size of collection costs of the authorized entity. Therefore, there is no equivalence in the relations on payment of the fee, and therefore the fee has no compensatory character. In turn, the nature of the actions performed by the authorized entity on behalf of and in the interests of the public legal entity, excludes their absolute determi-nation by actions of the payer of the fee. The results of research may become a crucial point for future research of legal regulation of fees.Conclusions. If a public authority carries out activities related to implementation of governmental and authoritative powers, the fee is based on public law. If an activity can not be associated with implementation of governmental and authoritative powers, the fee can be subject to civil law regulation.